Direct photo-patterning on anthracene containing polymer for guiding stem cell adhesion. Issue 1 (December 2016) - You, Jungmok; Heo, June; Kim, Hyun; Kim, Eunkyoung
Abstract Background Various micropatterned surfaces capable of guiding the selective adhesion of biomolecules such as proteins and cells are of great interests in biosensor, diagnostics, drug screening, and tissue engineering. In this study, we described a simple photo-patterning method to prepare micro-patterned films for stem cell patterning using anthracene containing polymers (PMAn). This micro patterned polymer film was prepared by the facile photo-reaction of anthracene units in polymer backbone structure. Results The UV irradiation of PMAn through a photomask resulted in the quenching of fluorescent intensity as well as the changes in surface wettability from hydrophobic to hydrophilic surface. As a result, UV exposed regions of PMAn film show lower fluorescent intensity as well as higher proliferation rate of mesenchymal stem cells (MSCs) than unexposed region of PMAn film. Furthermore, the selective MSC attachment was clearly observed in the UV exposed regions of PMAn film. Conclusion We developed a simple cell patterning method with a fluorescent, biocompatible, and patternable polymer film containing anthracene units. This method provides a facile stem cell patterning method and could be extended to various patterning of biomaterials without labor-intensive preparation and no pre-treatment for complex interactions of cell-microenvironment.